Extension of the Lower Load Limit in Dieseline Compression Ignition Mode. (August 2015) - Wang, Buyu; Wang, Zhi; Shuai, Shijin; Yu, Linjun; Wang, Jianxin
Abstract: A study to extend the low load limit of the mixture of commercial gasoline and diesel in the compression mode is performed on a single cylinder diesel engine. The additional measures, like intake heating, rebreathing, negative valve overlap, are not employed. By adopting boosting, sweeping the injection pressure and varying the fuel octane number, the minimum fuelling rate and the minimum IMEP gained is compared. Besides, the thermal efficiency and emission results at these operation points are also discussed. The results illustrate that the high intake pressure, the low injection pressure and the low fuel octane number are very effective to extend low load limit. With these strategies, gasoline-type fuels can get the lowest load 0.07 MPa IMEP (0.14 MPa intake pressure and 20 MPa injection pressure) and successfully replace diesel at low load operation points in the compression mode. Increasing the intake pressure and reducing the injection pressure can significantly reduce the minimum fuelling rate and then the minimum IMEP. The minimum IMEP (0.34 MPa) of the calibration point on the original engine at test speed (1600 rpm) can be achieved by G80 without boosting. The combustion efficiency is influenced by the intake pressure and the injection pressure, however, the ISFC is more dependent on the engine load rather than other factors. If there is more over-lean mixture in cylinder when adjusting the experimental conditions, CO and HC emissions are higher. To satisfy the Euro VI regulation on NOx (<0.4 g/kWh), a small amount of EGR is needed to control NOx emission.